IDENTIFICATION OF ESSENTIAL OIL COMPONENTS FROM THE PEELS OF LIME (Citrus aurantifolia) AND KAFFIR LIME (Citrus hystrix) BASED ON GROWING ALTITUDE USING GC-MS - Yodi Ari Stiawan; Reni Silvia Nasution; Bhayu Gita Bhernama (Indonesian Journal of Environmental Sustainability, 2023)
Essential oils are oils whose components are generally volatile and are obtained from various types of plants and are the largest demand commodity in marketing circles. One of the essential oil-producing plants, namely lime (C. aurantifolia) and kaffir lime (C. hystrix) so that they are widely used by industry as raw materials for making medicines, cosmetics, and perfumes because they contain various components in them. However, the community only uses the fruit as a spice for cooking and drinks, while the skin is thrown away so that it becomes waste. This study aims to determine the effect of the height of the growing location on the essential oil components of the fruit peels of C. aurantifolia and C. hystrix as measured using GC-MS. The sampling method was carried out by simple random sampling, which was taken from several trees randomly at an altitude range of 0-100, 400-500, and 1,200-1,300 masl. The extraction method used is steam-water distillation at 100°C for 6 hours. The results of GC-MS identification showed that the essential oil from the skin of C. aurantifolia fruit contains 3 main components, namely dl-Limonene, 2-β-Pinene, and γ-Terpinene and the highest component is obtained at an altitude range of 400-500 masl. Meanwhile, C. hystrix contains 5 main components in the form of 2-β-Pinene, Sabinene, dl-Limonene, Citronella, and β-Citronellol and the highest component is obtained at an altitude range of 0-100 masl. GC-MS analysis showed that the volatile oil components of the fruit peels of C. auratifolia and C. hystrix were affected by the altitude of the growing location including temperature and humidity.